1992
DOI: 10.1111/j.1468-2958.1992.tb00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Relational Communication in Computer-Mediated Interaction

Abstract: This study involved an experiment of the effects of time and communication channel—asynchronous computer conferencing versus face‐to‐face meetings—on relational communication in groups. Prior research on the relational aspects of computer‐mediated communication has suggested strong depersonalizing effects of the medium due to the absence of nonverbal cues. Past research is criticized for failing to incorporate temporal and developmental perspectives on information processing and relational development. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
424
2
9

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 750 publications
(457 citation statements)
references
References 58 publications
(107 reference statements)
22
424
2
9
Order By: Relevance
“…The general consensus is that online media, when compared to more traditional media, tend to encourage higher levels of disclosure [1,3,5], although, as time goes on these differences tend to dissipate [6]. It may be that initial disclosure is greater as a result of the perceived psychological distance fostered by features of the online context (e.g., accessibility and a synchronicity of communication or a lag time in between messages).…”
Section: Disclosurementioning
confidence: 95%
See 1 more Smart Citation
“…The general consensus is that online media, when compared to more traditional media, tend to encourage higher levels of disclosure [1,3,5], although, as time goes on these differences tend to dissipate [6]. It may be that initial disclosure is greater as a result of the perceived psychological distance fostered by features of the online context (e.g., accessibility and a synchronicity of communication or a lag time in between messages).…”
Section: Disclosurementioning
confidence: 95%
“…Past research suggests that invoking privacy setting use may be a particularly challenging task [6,30,31] and clearly more than media context is involved in motivating privacy setting use. Further research examining what motivates use of privacy settings is needed.…”
Section: Privacy Settingsmentioning
confidence: 99%
“…Walther tested this theory (Walther 1993, Walther andBurgeon 1992) and found that though interpersonal impressions were formed more slowly with CMC, relationships developed in the same way as in face to face situations, even becoming more socially oriented in the online context. Though Gunawardena and Zittle (1997) claim that social presence in a CMC context focus on the group members' reactions to one another because the teacher acts as 'more of a facilitator than the main source of information', this paper describes a proactive role the teacher plays in developing a socially responsive discourse that models a combination of social encouragement with content discussion.…”
Section: Background Of the Studymentioning
confidence: 99%
“…As recognized in continued virtual team research, the issues of communication exchange and interpretation require significant analysis prior to the final introduction of a technical interaction solution (Walther and Burgoon 1992). The development of guidelines and warnings for organizations attempting to implement virtual teams is a common thread in virtual team research over the last decade (Pape 1996;Wardell 1998;Maruca 1998;Wenger and Snyder 2000).…”
Section: Introductionmentioning
confidence: 99%